The Expressive Function of the Images in the Third Grade Primary Reading Book - Hussein Rashak Khudhair ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The study aims to identify of the expressive function of the images in the third grade primary reading book. The researcher prepared an analysis form consisting of 10 paragraphs, Include special paragraphs for measuring recognition of the expressive function of a images. After designing and presenting it to the experts, and making the necessary modifications to be in its final form, and experimenting it on the expletory sample, which consisted of (10) images. After confirming the validity and reliability, the researcher applied to the sample, which numbered (15) Image from the total of the research community to (80) images, which the researcher deliberately chose using the statistical program (spss) to find out the results of the research in knowing the average of each of the paragraphs included in the scale and the overall average of the total of the paragraphs as well as calculating the difference between the averages. The results showed a weak indication that the image expressive function was weak towards the content’s text. The researcher recommended reviewing the images that obtained low percentages in the third grade primary reading book and relying on high-quality standards to design these images again, in a way that leads to the purpose of their existence, in addition to the content’s text in the textbook.